EFFECT OF SIT–AT–HOME ON ECONOMIC DEVELOPMENT IN ENUGU STATE - Eze, Michael Tochukwu; Eneh , Jeremiah Ejike; Enekwizu , Chigozie Arthur; Enechukwu , Chukwunonso Chiedozie (International Journal of Management and Allied Research (IJMAR), 2023)
The sit-at-home order imposed by an organization, the Indigenous People of Biafra (IPOB), has become a recurring word among the dwellers in Enugu State within the Southeastern part of Nigeria and as such, there is virtually non-movement of persons on specified days. Every Monday since mid-2021 has been marked as a non-movement day in the region pending the release of its leader, Mazi Nnamdi Kanu, from detention. With a sample of 1000 respondents in a survey research design, this study adopted descriptive techniques to examine the effects of sit-at-home on economic development in Enugu State in the year 2022. The results, supported by both descriptive statistics outcome and hypothesis test, revealed that economic development was negatively affected by the IPOB sit-at-home order. This study recommends that government should reach an agreement with the IPOB hierarchy to restore a sound business environment for the expected level of investment inflow in the Southeast region and Enugu State in particular